Tolerance response to in situ ammonia stress in a pilot-scale anaerobic digestion reactor for alleviating ammonia inhibition. (December 2015) - Gao, Shumei; Zhao, Mingxing; Chen, Yang; Yu, Meijuan; Ruan, Wenquan
Highlights: Stepwise in situ ammonia-tolerance acclimation was practical and successful. Anaerobic reactor worked well at an average ammonia concentration of 4275 mg/L. Specific CoF420 content was enhanced with increasing in situ ammonia stress. Microbial community shift from AM to HM was an in situ response to ammonia stress. Abstract: The anaerobic digestion (AD) of protein-rich substrates is generally inhibited by ammonia. In this study, ammonia-tolerant acclimation was exposed to a stepwise in situ ammonia stress during the continuous AD of solid residual kitchen waste by using a continuous stirred tank reactor with a 50 L active volume. The reactor worked well during the acclimation process, with an average daily biogas production of 58 L/d, an effluent soluble chemical oxygen demand of 7238 mg/L, a volatile fatty acid (VFA) content of 578 mg/L, and a VFA/alkalinity ratio of less than 0.4. Moreover, ammonia stress enhanced the activity of Coenzyme F420 . The results of high-throughput 16S rDNA sequencing showed that ammonia stress increased the relative abundance of Firmicutes bacteria and hydrogenotrophic methanogens but decreased the abundance of acetotrophic methanogens. This microbial community shift was proposed to be an in situ response strategy for ammonia stress adaptation.